Effect of nitric oxide on oxygenation and mortality in acute lung injury: systematic review and meta-analysis. Issue 7597 (23rd March 2007) - Adhikari, Neill K J; Burns, Karen E A; Friedrich, Jan O; Granton, John T; Cook, Deborah J; Meade, Maureen O
Abstract : Objective To review the literature on the use of inhaled nitric oxide to treat acute lung injury/acute respiratory distress syndrome (ALI/ARDS) and to summarise the effects of nitric oxide, compared with placebo or usual care without nitric oxide, in adults and children with ALI or ARDS. Design Systematic review and meta-analysis. Data sources Medline, CINAHL, Embase, and CENTRAL (to October 2006), proceedings from four conferences, and additional information from authors of 10 trials. Review methods Two reviewers independently selected parallel group randomised controlled trials comparing nitric oxide with control and extracted data related to study methods, clinical and physiological outcomes, and adverse events. Main outcome measures Mortality, duration of ventilation, oxygenation, pulmonary arterial pressure, adverse events. Results 12 trials randomly assigning 1237 patients met inclusion criteria. Overall methodological quality was good. Using random effects models, we found no significant effect of nitric oxide on hospital mortality (risk ratio 1.10, 95% confidence interval 0.94 to 1.30), duration of ventilation, or ventilator-free days. On day one of treatment, nitric oxide increased the ratio of partial pressure of oxygen to fraction of inspired oxygen (PaO2 /FiO2 ratio) (13%, 4% to 23%) and decreased the oxygenation index (14%, 2% to 25%). Some evidence suggested that improvements in oxygenation persisted until day four. There was no effect on mean pulmonary arterial pressure. Patients receiving nitric oxide had an increased risk of developing renal dysfunction (1.50, 1.11 to 2.02). Conclusions Nitric oxide is associated with limited improvement in oxygenation in patients with ALI or ARDS but confers no mortality benefit and may cause harm. We do not recommend its routine use in these severely ill patients.